Christian Religious Education Teacher’s Understanding of Humanist Education: Case Study in Kanaan Jakarta Junior and Senior High School - Samosir, Christina Metallica; Boiliu, Noh Ibrahim (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2023)
Kanaan Junior High School and Senior High School in Jakarta are Christian schools whose teachers are Christian. Christian teachers must understand humanist education and apply it according to the Christian faith. Christian teachers at Kanaan Jakarta Junior School and High School are not limited to knowledge. The learning process is part of developing human values. Teachers should understand children as unique individuals. This view of the uniqueness of the individual leads teachers to emphasize education as an effort to find personal meaning in students. Education functions to help individuals become independent and responsible human beings in choosing. This study was to determine the understanding of the Christian faith so that Christian teachers at Kanaan Jakarta Junior School and High School about humanist education based on Deuteronomy 6:5 in the learning process. The method used is the descriptive qualitative method. Christian teachers at Kanaan School Jakarta have understood Deuteronomy 6:5 as the basis for humanist education in the learning process, applied the principle of love in the learning process, implemented humanist-based education, and taught technology, to use communicative methods in the teaching and learning process. In learning, the teacher has acted as an evaluator and facilitator.